Electrochemical grafting of aryl diazonium salts in deep eutectic solvents. (10th February 2021) - Lenne, Quentin; Andrieux, Vivien; Levanen, Gaël; Bergamini, Jean-Francois; Nicolas, Pauline; Paquin, Ludovic; Lagrost, Corinne; Leroux, Yann R.
Abstract: Deep eutectic solvents are seen as a new class of green and cheap solvents in electrochemical processes. Many electrochemical deposition techniques have been reported in the literature mainly focusing on metal electrodeposition and electro-polymerization. Here, we report for the first time the efficient electro-grafting of aryl diazonium salts on carbon surfaces using ethaline as an example of a natural and biodegradable deep eutectic solvent. Three different aryl diazonium salts have been tested, namely the 4-iodophenyldiazonium ion, 4-carboxymethylphenyl diazonium ion and 4-ethynylphenyldiazonium ion. Effect of concentration, deposition time and potential have been studied in relation to electrode blocking behavior toward redox probes in solution and deposited organic films thickness. Post-functionalization with redox active moieties is demonstrated on such electro-grafted organic layer to show their potential usefulness.